Utilization of Jatropha curcas Seed Meal and its Limitation as Feed Ingredient - Wina, Elizabeth; IWR, Susana; Pasaribu, Tiurma (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
One of the alternatives to solve the problem of less fossil energy is to utilize plant as a new source of energy, i.e Jatropha curcas, known as physic nut. This plant has been promoted as a source of energy as its seed contains high level of oil which can be used as biodiesel. The meal produced after pressing the seed will become a by product which contains high level of protein but also contains several anti nutritive factors or toxic compounds. This causes a problem to utilize this seed meal for animal feed. This paper descibes the nutritional quality and anti nutritive factors of jatropha seed meal, detoxification of jatropha seed meal and its utilization as feed ingredient and the problem of its utilization. Jatropha seed meal as a feed ingredient has to go through a combination process of detoxification. There is a need to find a cheap and easy detoxification technology to produce a safe and high nutritional quality of jatropha seed meal for animal. Â  Key words: Jatropha curcas, anti nutritive factors, detoxification, utilization, problem